Clonazepam monotherapy for treating people with newly diagnosed epilepsy - Brigo, Francesco (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the efficacy and tolerability of oral clonazepam used as monotherapy for newly diagnosed epilepsy, when compared with placebo or a different anti‐seizure medication.